Citizens, Experts, and the Environment : The Politics of Local Knowledge - Fischer, Frank, 1942- (Book collections on Project MUSE., 2000)
Claims that the problematic communication gap between experts and ordinary citizens is best remedied by a renewal of local citizen participation in deliberative structures.